New firms entry, labor reallocation, and institutions in transition economies - Randolph Luca Bruno (IZA World of Labor, 2015)
In the transition from central planning to a market economy in the 1990s, governments focused on privatizing or closing state enterprises, reforming labor markets, compensating laid-off workers, and fostering job creation through new private firms. After privatization, the focus shifted to creating a level playing-field in the product market by protecting property rights, enforcing the rule of law, and implementing transparent start-up regulations. A fair, competitive environment with transparent rules supports long-term economic growth and employment creation through the reallocation of jobs in favor of new private firms.
Keywords: J45; J63; J64; L26; P26; P31; 330; new firms entry; job reallocation; transition; institutions